2001
DOI: 10.1021/ma0019656
|View full text |Cite
|
Sign up to set email alerts
|

Oxadiazole Containing Conjugated−Nonconjugated Blue and Blue-Green Light Emitting Copolymers

Abstract: A series of segmented copolymers containing oxadiazole groups in the conjugated main chain have been synthesized with the objective of raising the electron transport ability. The present copolymers consist of alternating blocks of rigid chromophores containing oxadiazole units together with flexible spacer segments. The effects of chromophore substituents on the optical properties of the copolymers were investigated. Strong solvatochromic effects were observed, indicating intramolecular charge transfer in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…There have been several reports on the improvement of p-conjugated polymers such as PPV and polyfluorene by introducing hole-transporting and/or electron-transporting groups to realize highly efficient electroluminescence [9][10][11][12][13][14][15][16][17]. For example, Jin et al reported PPV-based copolymers containing an oxadiazole group with an electron injecting and transporting ability [9].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports on the improvement of p-conjugated polymers such as PPV and polyfluorene by introducing hole-transporting and/or electron-transporting groups to realize highly efficient electroluminescence [9][10][11][12][13][14][15][16][17]. For example, Jin et al reported PPV-based copolymers containing an oxadiazole group with an electron injecting and transporting ability [9].…”
Section: Introductionmentioning
confidence: 99%
“…The emitting wavelength is mainly determined by the effective π‐conjugation length in the excited state and by nonresonant or resonant coupling to surrounding electronic oscillators 7. Furthermore, block copolymers with isolated alternating segments have been synthesized to control the emitting wavelength 8–11. These copolymers provide efficient exciton confinement because of the microphase‐separated domain structure, and by the appropriate selection of chromophores, they can provide emissions at any selected portion of the spectrum 12…”
Section: Introductionmentioning
confidence: 99%
“…One way, used by Hay and Klavetter [200] and by Karasz and coworkers [201][202][203] proceeds by the linkage of a functional phenylene vinylene segment (commonly 3 units) with flexible spacers. These copolymers have been prepared by Wittig or Knoevenagel polycondensations and emit in the blue region [200][201][202][203], but the emission spectra are broadened due to the dilution effect of the chromophores by the insulating spacers. Green and yellow emissions have also been produced by copolymers of cyano-containing PPV-based chromophores and a flexible spacer as shown for the yellow light-emitting polymer XVII [201].…”
Section: Structure-emission Color Relationshipsmentioning
confidence: 99%